An appraisal of nitrogen and mineral content of forages selected by small ruminants in the humid zone of Nigeria - Carew, B.A.R. (International Livestock Centre for Africa, 1982)
Presents a comparative analysis of the nitrogen and mineral content of grasses, herbs, shrubs & trees selected by grazing animals during the late dry, early wet, late wet & early dry seasons in south western Nigeria, identifying mineral imbalances in the diets that might be contributing factors to the observed low productivity of sheep & goats; also examines the influence of geographic zone on mineral composition of forages.